Meningkatkan Minat Belajar Siswa Menggunakan Teknologi Komik Digital (Canva) pada Pembelajaran Bahasa Indonesia Kelas VII di SMP Negeri 13 Surabaya - Lolita Dwi Kusuma Devi; Sueb Hadi (CV. Alim's Publishing, 2024)
The main objective of this research is to generate interest in learning among seventh grade students at SMP Negeri 13 Surabaya. Through the application of digital comic-based learning methods designed using Canva, this study aims to overcome students' low interest in learning which has an impact on their academic achievement. Using the Kemmis & McTaggart model of Classroom Action Research (PTK) approach, this study involved 30 students as research subjects. The main instrument used was a teacher assessment journal to observe the development of students' interest in learning descriptively. The results showed a significant increase in students' interest in learning after the application of digital comic-based learning methods. This can be seen from the increased enthusiasm, active participation, and interaction of students in the learning process. The findings underscore the potential of digital comics as an effective learning medium to increase students' learning motivation and contribute positively to their academic achievement. Hopefully, the results of this study can serve as a reference for teachers in designing more innovative and engaging learning.